Never love a highlander ebook - Banks, Maya (McCabe Trilogy, 2011)
Maya Banks, the New York Times bestselling author of romance and romantic suspense has captivated readers with her steamy Scottish historical novels, perfect for fans of Julie Garwood. In Never Love a Highlander, the youngest McCabe brother uses sword and seduction to save his clan—and seal his heart.   Caelen McCabe’s young, reckless heart nearly destroyed his clan. Now, putting family loyalty above all else, he steps up to marry his older brother’s jilted bride and salvage the uneasy alliance between two clans. While beautiful Rionna McDonald is a fit wife for any man, Caelen trusts no woman, especially not this sweet temptress who torments him with white-hot longing. As the sacrificial lamb in her father’s power game, Rionna will do her duty but vows to protect her heart and her pride from humiliation. Despite everything, though, the heat in Caelen’s touch melts her defenses, and she craves the sensual delights of a husband who guards his emotions as fiercely as his clan. But when the ultimate battle for the McCabe legacy is upon them, Rionna’s true warrior spirit emerges. She will risk the wrath of her father, the fury of her enemies, and her life to prove to Caelen that his wife’s love is too precious to lose.